2021
DOI: 10.18421/tem104-02
|View full text |Cite
|
Sign up to set email alerts
|

Review of the State-of-the-art Sewer Monitoring and Maintenance Systems Pune Municipal Corporation - A Case Study

Abstract: There is an increasing trend of using automated and robotic systems for the tasks that are hazardous or inconvenient and dirty for humans. Sewers maintenance and cleaning is such a task where robots are already being used for inspection of underground pipes for blockages and damage. This paper reviews the existing robotic systems and various platforms and algorithms along with their capabilities and limitations being discussed. A typical mid-size city in a developing country, Pune, India is selected in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In earlier work, a survey on sewer robotic systems and computer vision practices in sewer inspection works was carried out and that gave information about practical issues concerning sewerage systems under the Pune Municipal Corporation (PMC), India [ 11 ]. It was concluded that sewer blockage is the main issue of sewers in Pune and to date, there is no robust algorithm and robotic system available for both real-time detection and removal of sewer pipe blockages.…”
Section: Needs Of the S-bird Datasetmentioning
confidence: 99%
“…In earlier work, a survey on sewer robotic systems and computer vision practices in sewer inspection works was carried out and that gave information about practical issues concerning sewerage systems under the Pune Municipal Corporation (PMC), India [ 11 ]. It was concluded that sewer blockage is the main issue of sewers in Pune and to date, there is no robust algorithm and robotic system available for both real-time detection and removal of sewer pipe blockages.…”
Section: Needs Of the S-bird Datasetmentioning
confidence: 99%
“…This approach is intended for real-time implementation on mobile devices and other environments with limited resources, with the goal of effectively removing such blockages. Our primary emphasis is on the training of the single-stage YOLOv5 model using the S-BIRD dataset [20,21], which contains representative and critical multi-class images depicting prevalent sewer blockage scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability and durability of these networks are critical, given their interdependence with other systems. However, the retrofitting process of these networks can be intricate and multifaceted [2]. Over time, pipe networks experience deterioration, leading to various defects contingent upon factors such as the construction type of the pipes, environmental conditions, and the materials used.…”
Section: Introductionmentioning
confidence: 99%